Risk factors for Klebsiella pneumoniae carbapenemase (KPC) gene acquisition and clinical outcomes across multiple bacterial species - Mathers, A; Vegesana, K; German Mesner, I; Ainsworth, J; Pannone, A; Crook, D; Sifri, C; Sheppard, A; Stoesser, N; Peto, T; Walker, A; Eyre, D (Elsevier, 2020)
Introduction: Risk-factors for carbapenemase-producing Enterobacteriales (CPE) acquisition/infection and associated clinical outcomes have been evaluated in the context of clonal, species-specific outbreaks; equivalent analyses for complex, multi-species outbreaks, which are increasingly common, are lacking. Methods: We performed a case-control study of Klebsiella pneumoniae carbapenemase (KPC)-producing organism (KPCO) acquisition using electronic health records from inpatients in a US academic medical center and long-term acute care hospital (LTACH), Dec 2010-Jan 2017, with ongoing multi-species KPCO transmission despite a robust CPE screening program. Cases had a first KPCO-positive culture >48 hours after admission, and included colonisations and infections (defined by clinical records). Controls had ≥2 negative peri-rectal screens and 40 no positive cultures. Risk-factors for KPCO acquisition, first infection following acquisition, and 14-day mortality following each infection episode were identified using multivariable logistic regression. Results: In 303 cases (89 with ≥1 infection) and 5929 controls, risk-factors for KPCO 44 acquisition included: longer inpatient stay, transfusion, complex thoracic pathology, 45 mechanical ventilation, dialysis, and exposure to carbapenems and β-lactam/β-lactamase 46 inhibitors. Exposure to other KPCO-colonised patients was only a risk factor for acquisition in a single unit, suggesting that direct patient-to-patient transmission did not play a major role. There were 15 species of KPCO; 61 (20%) cases were colonised/infected with >1 species. 14 day mortality following non-urinary KPCO infection was 20% (20/97 episodes) and was associated with failure to achieve source control. Conclusions: Healthcare exposures, antimicrobials and invasive procedures increased risk of KPCO colonisation/infection suggesting potential targets for infection control interventions in multi-species outbreaks. Evidence for patient-to-patient transmission was limited.